Pengaruh Motivasi Wirausaha dan Mental Wirausaha terhadap Minat Wirausaha - Pradana, Bayu Ilham; Safitri, Rini (IQTISHODUNA, 2020)
Indonesia is the lowest entrepreneurial climate in the world based on The Ernest and Young G20 Entrepreneurship Barometer 2013. The number of micros, small and medium enterprises has indeed increased from 2010 to 2015, but when viewed from the growth number shows the opposite. This is due to failure in entrepreneurship, with many factors causing it, one of which is mental entrepreneurship. This study entered the explanatory research category by collecting data using questionnaires. Then the data is processed using PLS, then the results are analyzed. The results of this study indicate that entrepreneurial mentality mediates the influence of entrepreneurial motivation on entrepreneurial interests. Thus it can be interpreted that with the increasing entrepreneurial mentality, the business interests of the students of the UB Entrepreneurship S1 Faculty of Economics and Business Study Program are also getting higher